Upregulation of SIRT1 by Kartogenin Enhances Antioxidant Functions and Promotes Osteogenesis in Human Mesenchymal Stem Cells. (15th July 2018) - Wang, Yifan; Chen, Guangdong; Yan, Jinku; Chen, Xi; He, Fan; Zhu, Caihong; Zhang, Junxin; Lin, Jun; Pan, Guoqing; Yu, Jia; Pei, Ming; Yang, Huilin; et al.
Abstract : Osteoarthritis is a chronic degenerative joint disease involving both articular cartilage and subchondral bone. Kartogenin (KGN) was recently identified to improve in vivo cartilage repair; however, its effect on bone formation is unknown. The aim of this study was to investigate the effect of KGN on antioxidant properties and osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BM-MSCs). Human BM-MSCs were treated with KGN at concentrations ranging from 10 −8  M to 10 −6  M. Our results indicated that KGN improved cell proliferation and attenuated intracellular reactive oxygen species. The levels of antioxidant enzymes and osteogenic differentiation of BM-MSCs were enhanced by KGN in a dose-dependent manner. Furthermore, KGN-treated BM-MSCs showed upregulation of silent information regulator type 1 (SIRT1) and increased phosphorylation of adenosine 5 ′ -monophosphate-activated protein kinase (AMPK), indicating that KGN activated the AMPK-SIRT1 signaling pathway in BM-MSCs. Inhibition of SIRT1 by nicotinamide reversed the antioxidant effect of KGN on BM-MSCs and suppressed osteogenic differentiation. In conclusion, our results demonstrated that KGN improved intracellular antioxidant properties and promoted osteogenic differentiation of BM-MSCs by activating the AMPK-SIRT1 signaling pathway. Thus, KGN may have the potential for not only articular cartilage repair but also the clinical application of MSCs in bone tissue engineering.